Asset Trading Volume with Dynamically Complete Markets and Heterogeneous Agents - Judd, Kenneth L.; Kubler, Felix; Schmedders, Karl (Journal of Finance, 2003)
Abstract Trading volume of infinitely lived securities, such as equity, is generically zero in Lucas asset pricing models with heterogeneous agents. More generally, the end‐of‐period portfolio of all securities is constant over time and states in the generic economy. General equilibrium restrictions rule out trading of equity after an initial period. This result contrasts the prediction of portfolio allocation analyses that portfolio rebalancing motives produce nontrivial trade volume. Therefore, other causes of trade must be present in asset markets with large trading volume.